About this Journal Submit a Manuscript Table of Contents
Abstract and Applied Analysis
Volume 2011 (2011), Article ID 927690, 15 pages
http://dx.doi.org/10.1155/2011/927690
Research Article

Oscillation of Second-Order Neutral Functional Differential Equations with Mixed Nonlinearities

1School of Science, University of Jinan, Jinan, Shandong 250022, China
2Department of Mathematics and Statistics, Missouri University of Science and Technology, Rolla, MO 65409-0020, USA
3School of Control Science and Engineering, Shandong University, Jinan, Shandong 250061, China

Received 2 September 2010; Revised 26 November 2010; Accepted 23 December 2010

Academic Editor: Miroslava Ružicková

Copyright © 2011 Shurong Sun et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Abstract

We study the following second-order neutral functional differential equation with mixed nonlinearities (??(??)|(??(??)+??(??)??(??-??))'|??-1(??(??)+??(??)??(??-??))?)?+??0(??)|??(??0(??))|??-1??(??0(??))+??1(??)|??(??1(??))|??-1??(??1(??))+??2(??)|??(??2(??))|??-1??(??2(??))=0, where ??>??>??>0, ?8??0(1/??1/??(??))d??<8. Oscillation results for the equation are established which improve the results obtained by Sun and Meng (2006), Xu and Meng (2006), Sun and Meng (2009), and Han et al. (2010).

1. Introduction

This paper is concerned with the oscillatory behavior of the second-order neutral functional differential equation with mixed nonlinearities ?||??(??)(??(??)+??(??)??(??-??))?||??-1(??(??)+??(??)??(??-??))???+??0||?????(??)0?||(??)??-1?????0?(??)+??1||?????(??)1?||(??)??-1?????1?(??)+??2||?????(??)2?||(??)??-1?????2?(??)=0,??=??0,(1.1) where ??>??>??>0 are constants, ?????1([??0,8),(0,8)), ?????([??0,8),[0,1)), ???????([??0,8),R), ??=0,1,2, are nonnegative, ??=0 is a constant. Here, we assume that there exists ?????1([??0,8),R) such that ??(??)=????(??), ??(??)=??, lim???8??(??)=8, and ???(??)>0 for ??=??0.

One of our motivations for studying (1.1) is the application of this type of equations in real word life problems. For instance, neutral delay equations appear in modeling of networks containing lossless transmission lines, in the study of vibrating masses attached to an elastic bar; see the Euler equation in some variational problems, in the theory of automatic control and in neuromechanical systems in which inertia plays an important role. We refer the reader to Hale [1] and Driver [2], and references cited therein.

Recently, there has been much research activity concerning the oscillation of second-order differential equations [38] and neutral delay differential equations [920]. For the particular case when ??(??)=0, (1.1) reduces to the following equation: ?||||??(??)??(??)??-1???(??)?+??0||?????(??)0?||(??)??-1?????0?(??)+??1||?????(??)1?||(??)??-1?????1?(??)+??2||?????(??)2?||(??)??-1?????2?(??)=0,??=??0.(1.2)

Sun and Meng [6] established some oscillation criteria for (1.2), under the condition?8??01??1/??(??)d??<8,(1.3) they only obtained the sufficient condition [6, Theorem 5], which guarantees that every solution ?? of (1.2) oscillates or tends to zero.

Sun and Meng [7] considered the oscillation of second-order nonlinear delay differential equation?||????(??)?||(??)??-1????(??)?+??0||?????(??)0?||(??)??-1?????0?(??)=0,??=??0(1.4) and obtained some results for oscillation of (1.4), for example, under the case (1.3), they obtained some results which guarantee that every solution ?? of (1.4) oscillates or tends to zero, see [7, Theorem 2.2].

Xu and Meng [10] discussed the oscillation of the second-order neutral delay differential equation?||??(??)(??(??)+??(??)??(??-??))?||??-1(??(??)+??(??)??(??-??))???+??(??)??(??(??(??)))=0,??=??0(1.5) and established the sufficient condition [10, Theorem 2.3], which guarantees that every solution ?? of (1.5) oscillates or tends to zero.

Han et al. [11] examined the oscillation of second-order neutral delay differential equation?||??(??)??(??(??))(??(??)+??(??)??(??-??))?||??-1(??(??)+??(??)??(??-??))???+??(??)??(??(??(??)))=0,??=??0(1.6) and established some sufficient conditions for oscillation of (1.6) under the conditions (1.3) and??(??)=??-??.(1.7) The condition (1.7) can be restrictive condition, since the results cannot be applied on the equation???2???1??(??)+2???(??-2)??????+??2??+12??2??+2???(??-1)=0,??=??0.(1.8)

The aim of this paper is to derive some sufficient conditions for the oscillation of solutions of (1.1). The paper is organized as follows. In Section 2, we establish some oscillation criteria for (1.1) under the assumption (1.3). In Section 3, we will give three examples to illustrate the main results. In Section 4, we give some conclusions for this paper.

2. Main Results

In this section, we give some new oscillation criteria for (1.1).

Below, for the sake of convenience, we denote ???(??):=??(??)+??(??)??(??-??),??(??):=????01??1/??(??)d??,(2.1)??(??):=??1/???(??(??))????1?1???(??(??))1/???????(??)d??,0????(??):=1-??0(??)??????0(??),??1????(??):=1-??1(??)??????1??(??),2????(??):=1-??2(??)??????2??(??),0(??):=??0(?1??)?1+??(??(??))??,??1(??):=??1(?1??)?1+??(??(??))??,??2(??):=??2?1(??)?1+??(??(??))??,h0(??):=??0(?1??)?1+??(??)??,h1(??):=??1(?1??)?1+??(??)??,h2(??):=??2?1(??)?1+??(??)??,???(??):=8??(??)1??1/??(???)d??,??(??):=8??1??1/??(??)d??,??1:=??-????-??,??2:=??-??,??-????(??):=??0?(??)??(??)?1+??(??(??))??+??1?(??)??(??)?1+??(??(??))??+??2?(??)??(??)?1+??(??(??))??.(1)

Theorem 2.1. Assume that (1.3) holds, ???(??)=0, and there exists ?????1([??0,8),R), such that ??(??)=??, ???(??)>0, ????(??)=??(??)-??,??=0,1,2. If for all sufficiently large ??1, ?8????????(??(??))0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?-?????(??)????-1(??(??))??1-1/??(??(??))????(????)d??=8,(2.2)8????0???(??)+1??1?(??)1/??1???2??2?(??)1/??2????????(??)-???+1??+1???(??)??(??)??1/???(??(??))d??=8,(2.3) then (1.1) is oscillatory.

Proof. Suppose to the contrary that ?? is a nonoscillatory solution of (1.1). Without loss of generality, we may assume that ??(??)>0 for all large ??. The case of ??(??)<0 can be considered by the same method. From (1.1) and (1.3), we can easily obtain that there exists a ??1=??0 such that ??(??)>0,????||??(??)>0,??(??)?||(??)??-1????(??)?=0,(2.4) or ??(??)>0,????||??(??)<0,??(??)?||(??)??-1????(??)?=0.(2.5) If (2.4) holds, we have ?????(??)??(??)?????=??(??(??))??(??(??))??,??=??1.(2.6) From the definition of ??, we obtain ??(??)=??(??)-??(??)??(??-??)=??(??)-??(??)??(??-??)=(1-??(??))??(??).(2.7) Define ??(??)=????(?????(??))??(??)??(??)??(??(??(??)))??,??=??1.(2.8) Then, ??(??)>0 for ??=??1. Noting that ???(??)>0, we get ??(????(??))=??(??(??)) for ??=0,1,2. Thus, from (1.1), (2.7), and (2.8), it follows that ???(??)=?????(??)????-1(??(??))??1/?????(??(??))??(??)??(??)??(??(??(??)))??-????(??????(??))1-??0(??)??????0(??)-????(???????(??))1-??1(??)??????1(??)????-??(??????(??))+1-??2(??)??????2(??)????-??(???(??))-?????????(??(??))??(??)??(??)??(??(??(??)))??+1???(??(??))???(??).(2.9) By (2.4), (2.9), and ???(??)>0, we get ???(??)=?????(??)????-1(??(??))??1/?????(??(??))??(??)??(??)??(??(??(??)))??-????(??????(??))1-??0(??)??????0(??)-????(???????(??))1-??1(??)??????1(??)????-??(??????(??))+1-??2(??)??????2(??)????-??(?.??(??))(2.10) In view of (2.4), (2.6), and (2.10), we have ???(??)=?????(??)????-1(??(??))??1/?????(??(??))??(??(??))??(??(??))??(??(??(??)))??-????(??????(??))1-??0(??)??????0(??)-????(???????(??))1-??1(??)??????1(??)????-??(??????(??))+1-??2(??)??????2(??)????-??(?.??(??))(2.11) By (2.4), we obtain ????????(??(??))=??1+???????1???(??(??))???(????????)d??=??1+???????1?1???(??(??))1/????????(??(??))?(???(??))???1/?????(??)d??=??1/??(??(??))???(???(??))????1?1???(??(??))1/?????(??)d??,(2.12) that is, ??(??(??))=??(??)???(??(??)).(2.13) Set ?????:=1??1(??)????-???(??(??))1/??1???,??:=2??2(??)????-???(??(??))1/??2,??:=??1,??:=??2.(2.14) Using Young’s inequality ||||=1??????|??|??+1??||??||??1,??,???R,??>1,??>1,??+1??=1,(2.15) we have ??1(??)????-??(??(??))+??2(??)????-?????(??(??))=1??1?(??)1/??1???2??2?(??)1/??2.(2.16) Hence, by (2.11), (2.13), and (2.16), we obtain ???(??)=?????(??)????-1(??(??))??1-1/??(??(??))????(??)-???????(??(??))0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?.(2.17) Integrating (2.17) from ??1 to ??, we get ???0<??(??)=??1?,(2.18)-?????1????????(??(??))0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?-?????(??)????-1(??(??))??1-1/??(??(??))????(???)d??.(2.19) Letting ???8 in (2.19), we get a contradiction to (2.2). If (2.5) holds, we define the function ?? by ???(??)=??(??)-????(??)??-1???(??)????(??(??)),??=??1.(2.20) Then, ??(??)<0 for ??=??1. It follows from [??(??)|???(??)|??-1???(??)]?=0 that ??(??)|???(??)|??-1???(??) is nonincreasing. Thus, we have ??1/??(??)???(??)=??1/??(??)???(??),??=??.(2.21) Dividing (2.21) by ??1/??(??) and integrating it from ??(??) to ??, we obtain ??(??)=??(??(??))+??1/??(??)????(??)????(??)d????1/??(??),??=??(??).(2.22) Letting ???8 in the above inequality, we obtain 0=??(??(??))+??1/??(??)???(??)??(??),??=??1,(2.23) that is, ??1/????(??)??(??)?(??)??(??(??))=-1,??=??1.(2.24) Hence, by (2.20), we have -1=??(??)????(??)=0,??=??1.(2.25) Differentiating (2.20), we get ?????(??)=??(??)-????(??)??-1????(??)??????(??(??))-????(??)-????(??)??-1???(??)????-1(??(??))???(??(??))???(??)??2??(??(??)),(2.26) by the above equality and (1.1), we obtain ???(??)=-??0??(??)?????0?(??)????(??(??))-??1??(??)?????1?(??)????(??(??))-??2??(??)?????2?(??)????-?(??(??))????(??)-????(??)??-1???(??)????-1(??(??))???(??(??))???(??)??2??.(??(??))(2.27) Noticing that ???(??)=0, from [10, Theorem 2.3], we see that ???(??)=0 for ??=??1, so by ????(??)=??(??)-??, ??=0,1,2, we have ???????0?(??)????=??????(??(??))0?(??)???(??(??))+??(??(??))??(??(??)-??)??=?1??????(??(??))/??0????(??)??+??(??(??))??(??(??)-??)/??0?(??)????=?1?1+??(??(??))??,???????1?(??)????=??????(??(??))1?(??)???(??(??))+??(??(??))??(??(??)-??)??????-??=?1(??(??))??????(??(??))/??1????(??)??+??(??(??))??(??(??)-??)/??1?(??)????????-??=?1(??(??))?1+??(??(??))??????-?????(??(??)),?????2?(??)/?????=??????(??(??))2?(??)???(??(??))+??(??(??))??(??(??)-??)??????-??=?1(??(??))??????(??(??))/??2????(??)??+??(??(??))??(??(??)-??)/??2?(??)????????-??=?1(??(??))?1+??(??(??))??????-??(??(??)).(2.28) On the other hand, from (??(??)(-???(??))??-1???(??))?=0, ??(??)=??, we obtain ?????(??(??))=1/??(??)??1/????(??(??))?(??).(2.29) Thus, by (2.20) and (2.27), we get ??????(??)=-0(??)+??1(??)????-??(??(??))+??2(??)????-???-(??(??))?????(??)??1/??(??(??))(-??(??))(??+1)/??.(2.30) Set ?????:=1??1(??)????-???(??(??))1/??1???,??:=2??2(??)????-???(??(??))1/??2,??:=??1,??:=??2.(2.31) Using Young’s inequality (2.15), we obtain ??1(??)????-??(??(??))+??2(??)????-?????(??(??))=1??1?(??)1/??1???2??2?(??)1/??2.(2.32) Hence, from (2.30), we have ??????(??)=-0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?-?????(??)??1/??(??(??))(-??(??))(??+1)/??,(2.33) that is, ??????(??)+0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?+?????(??)??1/??(??(??))(-??(??))(??+1)/??=0,??=??1.(2.34) Multiplying (2.34) by ????(??) and integrating it from ??1 to ?? implies that ????(??)??(??)-???????1??????1??+??????1??-1/??(??(??))???(??)????-1(+???)??(??)d??????1???0???(??)+1??1?(??)1/??1???2??2?(??)1/??2??????(??)d??+??????1????(??)???(??)??1/??(??(??))(-??(??))(??+1)/??d??=0.(2.35) Set ??:=(??+1)/??, ??:=??+1, and ??:=(??+1)??/(??+1)????2/(??+1)??(??)??(??),??:=(??+1)??/(??+1)??-1/(??+1)(??).(2.36) Using Young's inequality (2.15), we get -??????-1(??)??(??)=??????(??)(-??(??))(??+1)/??+??????+1??+11.??(??)(2.37) Thus, -?????(??)????-1(??)??(??)??1/??(??(??))=???????(??)??(??)(-??(??))(??+1)/????1/??(??(??))+??????(??)???+1??+11??(??)??1/??(??(??)).(2.38) Therefore, (2.35) yields ????(??)??(??)=???????1??????1?,-?????1????0???(??)+1??1?(??)1/??1???2??2?(??)1/??2????????(??)-???+1??+1???(??)??(??)??1/???(??(??))d??.(2.39) Letting ???8 in the above inequality, by (2.3), we get a contradiction with (2.25). This completes the proof of Theorem 2.1.

From Theorem 2.1, when ??(??)=??, we have the following result.

Corollary 2.2. Assume that (1.3) holds, ???(??)=0, and ????(??)=??-??, ??=0,1,2. If for all sufficiently large ??1 such that (2.2) holds and ?8??h0???(??)+1h1?(??)1/??1???2h2?(??)1/??2????????(??)-???+1??+11??(??)??1/???(??)d??=8,(2.40) then (1.1) is oscillatory.

Theorem 2.3. Assume that (1.3) holds, ???(??)=0, and there exists ?????1([??0,8),R), such that ??(??)=??, ???(??)>0, ????(??)=??(??)-??, ??=0,1,2. If for all sufficiently large ??1 such that (2.2) holds and ?8???0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?????+1(??)d??=8,(2.41) then (1.1) is oscillatory.

Proof. Suppose to the contrary that ?? is a nonoscillatory solution of (1.1). Without loss of generality, we may assume that ??(??)>0 for all large ??. The case of ??(??)<0 can be considered by the same method. From (1.1) and (1.3), we can easily obtain that there exists a ??1=??0 such that (2.4) or (2.5) holds.
If (2.4) holds, proceeding as in the proof of Theorem 2.1, we obtain a contradiction with (2.2).
If (2.5) holds, we proceed as in the proof of Theorem 2.1, then we get (2.25) and (2.34). Multiplying (2.34) by ????+1(??) and integrating it from ??1 to ?? implies that ????+1(??)??(??)-????+1???1??????1??+(??+1)????1??-1/??(??(??))???(??)????(+???)??(??)d??????1???0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?????+1?(??)d??+??????1????+1(??)???(??)??1/??(??(??))(-??(??))(??+1)/??d??=0.(2.42) In view of (2.25), we have -??(??)????+1(??)=??(??)<8, ???8. From (1.3), we get ?????1-??-1/??(??(??))???(??)?????(??)??(??)d??=????1??-1/??(??(??))????(??)d??=??(??)??(??1)??-1/???(??)d??<8,???8,????1????+1(??)???(??)??1/??((??(??))-??(??))(??+1)/???d??=???????(??)1???-1/??(??)d??<8,???8.(2.43) Letting ???8 in (2.42) and using the last inequalities, we obtain ?8???0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?????+1(??)d??<8,(2.44) which contradicts (2.41). This completes the proof of Theorem 2.3.

From Theorem 2.3, when ??(??)=??, we have the following result.

Corollary 2.4. Assume that (1.3) holds, ???(??)=0, ????(??)=??-??, ??=0,1,2. If for all sufficiently large ??1 such that (2.2) holds and ?8?h0???(??)+1h1?(??)1/??1???2h2?(??)1/??2?????+1(??)d??=8,(2.45) then (1.1) is oscillatory.

Theorem 2.5. Assume that (1.3) holds, ???(??)=0, and there exists ?????1([??0,8),R), such that ??(??)=??, ???(??)>0, ????(??)=??(??)-??, ??=0,1,2. If for all sufficiently large ??1 such that (2.2) holds and ?8??1??-1/????(??)????1???(??)d??1/??d??=8,(2.46) then (1.1) is oscillatory.

Proof. Suppose to the contrary that ?? is a nonoscillatory solution of (1.1). Without loss of generality, we may assume that ??(??)>0 for all large ??. The case of ??(??)<0 can be considered by the same method. From (1.1) and (1.3), we can easily obtain that there exists a ??1=??0 such that (2.4) or (2.5) holds.
If (2.4) holds, proceeding as in the proof of Theorem 2.1, we obtain a contradiction with (2.2).
If (2.5) holds, we proceed as in the proof of Theorem 2.1, and we get (2.21). Dividing (2.21) by ??1/??(??) and integrating it from ??(??) to ??, letting ???8, yields ??(??(??))=-??1/??(??)????(??)8??(??)??-1/??(??)d??=-??1/??(??)???(??)??(??)=-??1/?????1???????1???(??):=????(??).(2.47) By (1.1), we have ????(??)-????(??)????=??0(??)???????0?(??)+??1(??)???????1?(??)+??2(??)???????2?(??).(2.48) Noticing that ???(??)=0, from [10, Theorem 2.3], we see that ???(??)=0 for ??=??1, so by ????(??)=??(??)-??, ??=0,1,2, we get ????????(??)=???????(??(??))???(??)=1??(??(??))+??(??(??))??(??(??)-??)??????(??(??))/????(??????)??+??(??(??))??(??(??)-??)/????(=1??)??.1+??(??(??))(2.49) Hence, we obtain ????(??)-????(??)????=????(??),(2.50) where ??=min{????,????,????}. Integrating the above inequality from ??1 to ??, we have ???(??)-???(???)?????=??1??-??????1?????+??????1???(??)d??=??????1??(??)d??.(2.51) Integrating the above inequality from ??1 to ??, we obtain ?????1?-??(??)=??1/???????1??-1/????(??)????1???(??)d??1/??d??,(2.52) which contradicts (2.46). This completes the proof of Theorem 2.5.

3. Examples

In this section, three examples are worked out to illustrate the main results.

Example 3.1. Consider the second-order neutral delay differential equation (1.8), where ??>0 is a constant.
Let ??(??)=e2??, ??(??)=1/2, ??=2, ??0(??)=??(2e2??+e2??+2)/2, ??=1, ??0(??)=??-1, ??1(??)=??2(??)=0, and ??(??)=??0(??), then ???(??)=????01??1/???e(??)d??=-2??0-e-2???2,??(??)=??1/???(??(??))????1?1???(??(??))1/??????e(??)d??=2(??-??1)?-12,??0??(??)=0(??)2=???2e2??+e2??+2?4,??0(??)=2??0(??)3=???2e2??+e2??+2?3.(3.1)
Setting ??(??)=??+1, we have ??0(??)=??-1=??(??)-??, ??(??)=e-2??-2/2. Therefore, for all sufficiently large ??1, ?8????????(??(??))0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?-?????(??)????-1(??(??))??1-1/??(??(??))????(????)d??=8,8????0???(??)+1??1?(??)1/??1???2??2?(??)1/??2????????(??)-???+1??+1???(??)??(??)??1/???=?(??(??))d??8???2e-2?+1-36d??=8(3.2) if ??>3/(2e-2+1). Hence, by Theorem 2.1, (1.8) is oscillatory when ??>3/(2e-2+1).
Note that [11, Theorem 2.1] and [11, Theorem 2.2] cannot be applied in (1.8), since ??0(??)>??-2. On the other hand, applying [11, Theorem 3.2] to that (1.8), we obtain that (1.8) is oscillatory if ??>3/(e-2+2e-4). So our results improve the results in [11].

Example 3.2. Consider the second-order neutral delay differential equation ?e???1??(??)+2???????-4?????v+1265e?????1??-8varcsin65?65=0,??=??0.(3.3) Let ??(??)=e??, ??(??)=1/2, ??=??/4, ??0v(??)=1265e??, ??1(??)=??2(??)=0,??=1,??0v(??)=??-(arcsin65/65)/8, ??(??)=??+??/4, and ??(??)=??-??/4, then ???(??)=????01??1/??(??)d??=e-??0-e-??,??(??)=??1/???(??(??))????1?1???(??(??))1/?????(??)d??=e??-??1??-1,0??(??)=0(??)2v=665e??,??0(??)=2??0(??)3v=865e??,??(??)=e-??-??/4.(3.4) Therefore, for all sufficiently large ??1, ?8????????(??(??))0???(??)+1??1?(??)1/??1???2??2?(??)1/??2?-?????(??)????-1(??(??))??1-1/??(??(??))????(????)d??=8,8????0???(??)+1??1?(??)1/??1???2??2?(??)1/??2????????(??)-???+1??+1???(??)??(??)??1/???=?(??(??))d??8?8v65e-??/4-14?d??=8.(3.5) Hence, by Theorem 2.1, (3.3) oscillates. For example, ??(??)=sin8?? is a solution of (3.3).

Example 3.3. Consider the second-order neutral differential equation ?e??????(??)?+e2??*???????0???+??1(??)??1/3???1???+??2(??)??5/3???2???=0,??=??0,(3.6) where ??(??)=??(??)+??(??-1)/2, ????>0 for ??=0,1,2, are constants, ??1(??)>0, ??2(??)>0 for ??=??0.
Let ??(??)=e??, ??=1, ??0(??)=e2??*??, ??*=max{??0,??1,??2}, ????(??)=??????, ??(??)=????, 0<??<min{??0,??1,??2,1}, ??(??)=??*??+1, ??=1, ??=1/3, and ??=5/3, then ??1=??2=2, ???(??)=????01??1/??(??)d??=e-??0-e-??,??(??)=??1/???(??(??))????1?1???(??(??))1/?????(??)d??=e??(??-??1)-1,??(??)=e-??*??-1.(3.7) It is easy to see that (2.2) and (2.41) hold for all sufficiently large ??1. Hence, by Theorem 2.3, (3.6) is oscillatory.

4. Conclusions

In this paper, we consider the oscillatory behavior of second-order neutral functional differential equation (1.1). Our results can be applied to the case when ????(??)>??, ??=0,1,2; these results improve the results given in [6, 7, 10, 11].

Acknowledgments

The authors sincerely thank the reviewers for their valuable suggestions and useful comments that have led to the present improved version of the original paper. This research is supported by the Natural Science Foundation of China (nos. 11071143, 60904024, 11026112), China Postdoctoral Science Foundation funded Project (no. 200902564), the Natural Science Foundation of Shandong (nos. ZR2010AL002, ZR2009AL003, Y2008A28), and also the University of Jinan Research Funds for Doctors (no. XBS0843).

References

  1. J. K. Hale, Theory of Functional Differential Equations, Springer, New York, NY, USA, 2nd edition, 1977. View at Zentralblatt MATH
  2. R. D. Driver, “A mixed neutral system,” Nonlinear Analysis: Theory, Methods & Applications, vol. 8, no. 2, pp. 155–158, 1984. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  3. R. P. Agarwal, S.-L. Shieh, and C.-C. Yeh, “Oscillation criteria for second-order retarded differential equations,” Mathematical and Computer Modelling, vol. 26, no. 4, pp. 1–11, 1997. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  4. B. Baculíková, “Oscillation criteria for second order nonlinear differential equations,” Archivum Mathematicum, vol. 42, no. 2, pp. 141–149, 2006. View at Zentralblatt MATH
  5. J. Džurina and I. P. Stavroulakis, “Oscillation criteria for second-order delay differential equations,” Applied Mathematics and Computation, vol. 140, no. 2-3, pp. 445–453, 2003. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  6. Y. G. Sun and F. W. Meng, “Oscillation of second-order delay differential equations with mixed nonlinearities,” Applied Mathematics and Computation, vol. 207, no. 1, pp. 135–139, 2009. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  7. Y. G. Sun and F. W. Meng, “Note on the paper of Džurina and Stavroulakis,” Applied Mathematics and Computation, vol. 174, no. 2, pp. 1634–1641, 2006. View at Publisher · View at Google Scholar
  8. S. Sun, Z. Han, P. Zhao, and C. Zhang, “Oscillation for a class of second-order Emden-Fowler delay dynamic equations on time scales,” Advances in Difference Equations, vol. 2010, Article ID 642356, 15 pages, 2010. View at Zentralblatt MATH
  9. B. Baculíková and D. Lacková, “Oscillation criteria for second order retarded differential equations,” Studies of the University of Žilina. Mathematical Series, vol. 20, no. 1, pp. 11–18, 2006.
  10. R. Xu and F. Meng, “Some new oscillation criteria for second order quasi-linear neutral delay differential equations,” Applied Mathematics and Computation, vol. 182, no. 1, pp. 797–803, 2006. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  11. Z. Han, T. Li, S. Sun, and Y. Sun, “Remarks on the paper [Appl. Math. Comput. 207 (2009) 388–396],” Applied Mathematics and Computation, vol. 215, no. 11, pp. 3998–4007, 2010. View at Publisher · View at Google Scholar
  12. Z. Han, T. Li, S. Sun, and W. Chen, “On the oscillation of second-order neutral delay differential equations,” Advances in Difference Equations, vol. 2010, Article ID 289340, 8 pages, 2010. View at Zentralblatt MATH
  13. R. Xu and F. Meng, “Oscillation criteria for second order quasi-linear neutral delay differential equations,” Applied Mathematics and Computation, vol. 192, no. 1, pp. 216–222, 2007. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  14. L. Liu and Y. Bai, “New oscillation criteria for second-order nonlinear neutral delay differential equations,” Journal of Computational and Applied Mathematics, vol. 231, no. 2, pp. 657–663, 2009. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  15. J.-G. Dong, “Oscillation behavior of second order nonlinear neutral differential equations with deviating arguments,” Computers & Mathematics with Applications, vol. 59, no. 12, pp. 3710–3717, 2010. View at Publisher · View at Google Scholar · View at Zentralblatt MATH
  16. Z. Han, T. Li, S. Sun, C. Zhang, and B. Han, “Oscillation criteria for a class of second order neutral delay dynamic equations of Emden-Fowler type,,” Abstract and Applied Analysis, vol. 2011, pp. 1–26, 2011.
  17. T. Li, Z. Han, P. Zhao, and S. Sun, “Oscillation of even-order neutral delay differential equations,” Advances in Difference Equations, vol. 2010, Article ID 184180, 9 pages, 2010.
  18. Z. Han, T. Li, S. Sun, and C. Zhang, “An oscillation criteria for third order neutral delay differential equations,” Journal of Applied Analysis, vol. 16, pp. 295–303, 2010.
  19. Y. Sun, Z. Han, T. Li, and G. Zhang, “Oscillation criteria for second-order quasilinear neutral delay dynamic equations on time scales,” Advances in Difference Equations, vol. 2010, Article ID 512437, 14 pages, 2010. View at Zentralblatt MATH
  20. Z. Han, T. Li, S. Sun, and W. Chen, “Oscillation criteria for second-order nonlinear neutral delay differential equations,” Advances in Difference Equations, vol. 2010, Article ID 763278, 23 pages, 2010.